2015
DOI: 10.1080/15384101.2015.1053667
|View full text |Cite
|
Sign up to set email alerts
|

A fluorescent bimolecular complementation screen reveals MAF1, RNF7 and SETD3 as PCNA-associated proteins in human cells

Abstract: These authors contributed equally to this work.Keywords: Bimolecular Fluorescence Complementation, DNA Replication, Maf1, PCNA, Protein interactions, RNF7, SetD3The proliferating cell nuclear antigen (PCNA) is a conserved component of DNA replication factories, and interactions with PCNA mediate the recruitment of many essential DNA replication enzymes to these sites of DNA synthesis. A complete description of the structure and composition of these factories remains elusive, and a better knowledge of them will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 79 publications
0
27
0
Order By: Relevance
“…SETD3 accumulates after the peak of cyclin E1, a critical regulator controlling G 1 /S transition, but before the induction of cyclin B1, a critical regulator of G 2 /M transition, implying that SETD3 functions from the S phase to G 2 phase. Consistently, a recent study showed that SETD3 interacted with proliferating cell nuclear antigen, a key component of the DNA replication machinery, indicating its potential roles in DNA replication and DNA repair (36). It has been reported that both zebrafish and mouse homologs of SETD3 may catalyze H3K4 or H3K36 mono-and dimethylation in vitro (31,32), and H3K4 and H3K36 methylations are associated with DNA replication and DNA repair (37-39).…”
Section: Discussionmentioning
confidence: 68%
“…SETD3 accumulates after the peak of cyclin E1, a critical regulator controlling G 1 /S transition, but before the induction of cyclin B1, a critical regulator of G 2 /M transition, implying that SETD3 functions from the S phase to G 2 phase. Consistently, a recent study showed that SETD3 interacted with proliferating cell nuclear antigen, a key component of the DNA replication machinery, indicating its potential roles in DNA replication and DNA repair (36). It has been reported that both zebrafish and mouse homologs of SETD3 may catalyze H3K4 or H3K36 mono-and dimethylation in vitro (31,32), and H3K4 and H3K36 methylations are associated with DNA replication and DNA repair (37-39).…”
Section: Discussionmentioning
confidence: 68%
“…Additionally, Pol III activity may be affected by other players modulating the MAF1 effect, such as the previously proposed casein kinase 2 (Boguta and Graczyk 2011), or by putative MAF1 binding partners brought in close proximity of Pol III genes. For example, MAF1 has recently been shown to interact with PCNA (Cooper et al 2015), a member of the DNA sliding clamp family with the ability to inhibit EP300 acetyltransferase activity (Hong and Chakravarti 2003). It is conceivable that MAF1-delivered PCNA could repress transcription of Pol III, which contains a PCNA binding site in the POLR3E (Rpc5) subunit (Gilljam et al 2009), by preventing histone acetylation in the vicinity of Pol III genes.…”
Section: A Model For Maf1 Repression Of Transcribing Pol IIImentioning
confidence: 99%
“…SETD3 expression is lower in renal cell tumors than normal renal tissues, and low expression of SETD3 is associated with shorter survival in renal cell carcinoma patients [118]. SETD3 has been implicated in DNA replication and repair due to its interaction with proliferating cell nuclear antigen, a conserved factor involved in DNA synthesis [119].…”
Section: Ash1l: Hox Gene Activator With Emerging Role In Cancermentioning
confidence: 99%
“…SETD3 expression is lower in renal cell tumors than normal renal tissues, and low expression of SETD3 is associated with shorter survival in renal cell carcinoma patients [118]. SETD3 has been implicated in DNA replication and repair due to its interaction with proliferating cell nuclear antigen, a conserved factor involved in DNA synthesis [119].H3K36-specific SET domains: structural considerations for inhibitor development Structural details of target proteins are extremely valuable in the development of potent and specific inhibitors. For the H3K36-specific KMTases, structural studies of the catalytic SET domain have revealed valuable information to jumpstart inhibitor development.…”
mentioning
confidence: 99%